The Perceived Impact of the 2016 Election: A Mediation Model Predicting Health Outcomes - Koerten, Hannah Rose; Bogusch, Leah Michelle; Varga, Aniko Viktoria; O’Brien, William H. (Journal of Social and Political Psychology, 2019)
The present study examined the relationship between the self-reported personal impact of the election of President Donald J. Trump, as measured by the Personal Impact of the Election Scale (PIES), and physical and mental health. A sample of 299 MTurk Amazon workers completed an online survey, including measures of the perceived personal impact of the 2016 presidential election, thought suppression, and mental and physical health. A mediation model was tested, with thought suppression included as a mediator of the relationship between the PIES and physical and mental health. Results indicated that thought suppression partially mediated the relationship between the PIES and physical and mental health. Specifically, the perceived impact of the election was positively associated with thought suppression (β = .51, SE = .01, p < .001), which was in turn negatively associated with physical health (β = -.25, SE = .44, p < .001) and mental health (β = -.50, SE = .47, p < .001). The results of this study suggest that perceptions of this sociopolitical event were related to the health of United States citizens and show a need for large-scale interventions to address this relationship, especially for those who feel threatened based on their ethnic or religious background.